A Comprehensive Review of Serious Games in Health Professions. (3rd August 2014) - Ricciardi, Francesco; De Paolis, Lucio Tommaso
Abstract : Education of healthcare professionals is of primary importance for patient safety. In some health related professions, education and training have to be practiced during the entire working period and not only limited to school years. The use of new technology such as virtual reality and e-learning brings new possibilities with significant improvement in learning outcomes. Serious gaming describes a technology that can educate and train while entertaining users. This type of training can be very useful for health professions because it improves learning outcomes creating a learner oriented approach and providing a stealth mode of teaching. In some fields it represents an ideal instrument for continuous health professions education also in terms of costs because it is cheaper than traditional training methods that use cadavers or mannequins. In this paper we make a scoping review of serious games developed for health professions and health related fields in order to understand if they are useful tools for health related fields training. Many papers confirmed that serious gaming is a useful technology that improves learning and skills development for health professionals.